Tinjauan Sistematis untuk Mengoptimalisasi Pengalaman Pengguna Chatbot untuk Akses Layanan Mikro dan Keuangan Mikro pada UMKM - Fawwaz shabri Muttaqi; Agus Juhana (Jurnal Sistem Informasi dan Teknologi Informasi, 2025)
The objective of this research is to investigate implementation of chatbots in the microfinance and MSME sectors for better user experience and accessibility of public services. Systematic Literature Review (SLR) is applied in this article to review related articles with strict inclusion and exclusion criteria. In this sense, it was identified in an investigation with the aim of finding "chatbot"."conversational AI". "website" and "user satisfaction", restricting that, while chatbots have been studied extensively in other industries, there is limited scale of use Chatbots are not widely used on or by websites. Some of the major challenges observed are low digital literacy, restricted financial access and lack of personalization in user experience. Suggested interventions are enhancing chatbot personalisation, and increasing digital literacy while embedding chatbots with microfinance services. The paper serves to inform on the potential of chatbots for accelerating MSME digitalisation and financial inclusion in Indonesia and other emerging markets.